Tumor Cell-Secreted ISG15 Promotes Tumor Cell Migration and Immune Suppression by Inducing the Macrophage M2-Like Phenotype - Chen, Ren-Hui; Xiao, Zhi-Wen; Yan, Xiao-Qing; Han, Ping; Liang, Fa-Ya; Wang, Jing-Yi; Yu, Shi-Tong; Zhang, Ting-Zhen; Chen, Si-Qi; Zhong, Qian; Huang, Xiao-Ming (Frontiers in Immunology, 2020)
Interferon-stimulated gene 15 (ISG15) is known to be involved in tumor progression. We previously reported that ISG15 expressed on nasopharyngeal carcinoma (NPC) cells and related to poor prognosis of patients with NPC. We further observed that ISG15 can be secreted by NPC cell and expressed on the macrophages in situ. However, the role of ISG15 in tumor-associated macrophages (TAMs) remains poorly understood. In the present study, we found that ISG15 treatment induces macrophages with M2-like phenotype, and the enhancement of NPC cell migration and tumorigenicity. Mechanically, ISG15-induced M2-like phenotype is dependent on the interaction with its receptor, LFA-1, and engagement of SRC family kinase (SFK) signal, and the subsequent secretion of CCL18. Blocking LFA-1, or SRC signal with small molecular inhibitors, or neutralizing with anti-CCL18 antibody can impede the activation of LFA-1-SFK-CCL18 axis in ISG15-treated macrophages. Clinically, ISG15+ CD163+ TAMs related to impaired survival of patients and advanced tumor stage of NPC. Furthermore, we found ISG15+ CD163+ macrophages inhibited antitumor CD8+ cells responses in NPC. Together, our findings suggested tumor cell-secreted ISG15, which acted as a tumor microenvironmental factor, induces M2-like phenotype, promoting tumor progression and suppression of cytotoxic T lymphocyte response.